ЯдУУРЛЫГ БУУРУУЛаХ ТөРИйн БОдЛОГОд ТУЛГаМдаЖ БУй аСУУдаЛ - С.БАЗАРПҮРЭВ; Д.ГООМАРАЛ (Politology, 2023)
Definiting the poverty in a short way that the most simpliest feature to every person is the tactile of the low income and the spare comsumption.It must not be defined that the reason of the piverty is from social and economical factors. We must research individual factors.It is necessary to the researching of science and it is important to the decision making in state politics and implementing that politics.